2017
DOI: 10.1186/s13104-017-2977-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with Bartonella bacilliformis and Mycobacterium spp. in a coastal region of Peru

Abstract: Objective: This study investigated an outbreak of Bartonellosis in a coastal region in Peru.Results: A total of 70 (n = 70) samples with clinical criteria for the acute phase of Bartonellosis and a positive peripheral blood smear were included. 22.85% (n = 16) cases of the samples were positive for Bartonella bacilliformis by PCR and automatic sequencing. Of those positive samples, 62.5% (n = 10) cases were positive only for B. bacilliformis and 37.5% (n = 6) cases were positive to both Mycobacterium spp. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…B bacilliformis outbreaks usually occur in Andean communities, but they are now expanding to adjacent areas. [21][22][23] The implementation of serodiagnostic tools allowing broad epidemiological monitoring of Carrión's disease and the availability of a vaccine would be highly desirable; however, only a few immunogenic targets have been analysed. 6,10 Novel sequencing techniques and bioinformatics have revolutionised clinical microbiology and vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…B bacilliformis outbreaks usually occur in Andean communities, but they are now expanding to adjacent areas. [21][22][23] The implementation of serodiagnostic tools allowing broad epidemiological monitoring of Carrión's disease and the availability of a vaccine would be highly desirable; however, only a few immunogenic targets have been analysed. 6,10 Novel sequencing techniques and bioinformatics have revolutionised clinical microbiology and vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Peru found that 37.5% of Bartonellosis patients in an outbreak were infected with B. bacilliformis and Mycobacterium spp. [109]. While not necessarily co-transmitted, these infectious complications can exacerbate disease.…”
Section: Bartonella As a Coinfection In Humansmentioning
confidence: 99%